A performance analysis of batch fluidized bed drying of two pharmaceutical powders by desirability approach. Issue 6 (2nd May 2022) - Zammouri, Amel; Mihoubi, Nourhene Boudhrioua; Kechaou, Nabil
Abstract: In this work, a multi objective optimization of batch fluidized drying of two pharmaceutical powders (Group A particles and Group B particles) has been performed using desirability function. Optimization was studied based on non-linear models that take into account particle entrainment and combine dense bed and freeboard sections. Optimization criterion was simultaneously minimizing drying time, dense bed specific energy consumption, and freeboard specific energy consumption. The desired solid final moisture content was considered as a constraint. The control variables were air temperature and air velocity. For the Group B particles, simulation results indicated that desirability increase was monotonic with air temperature increase and air velocity decrease. For the Group A particles, it was shown, the existence of a desirability optimum. By comparing static and dynamic control to the real batch operation, the highest percent reduction of drying time, dense bed specific energy consumption, and freeboard specific energy consumption was obtained for static control with a high value of fixed inlet air temperature. Nevertheless, the risk of product overheating and damaging could be reduced by temperature reduction during the drying process as showed by optimal control trajectories obtained in the case of dynamic control.